2016
DOI: 10.1182/blood.v128.22.4545.4545
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Extracellular Vesicle Micrornas MiR-423, MiR-199 and MiR-93* As Biomarkers for Acute Graft Versus Host Disease

Abstract: Acute graft-versus-host disease (aGvHD) is a major cause of adverse outcome in hematopoietic stem cell transplantation (HSCT), with a high incidence (20-50%). A novel, non-invasive diagnostic test to predict for prevalence and severity would enable improved prophylaxis and reduce morbidity. Circulatory microRNAs (miRNAs) miR-423, miR-199, miR-93*, and miR-377 have previously been associated with aGvHD in post-HSCT patient plasma, but validation is lacking and their expression within extracellular vesicles (EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that expression of miR-93*/ miR-93-3p together with miR-423, miR-199a-3p and miR-377 in the plasma was able to predict the probability of aGvHD occurrence and was furthermore positively associated with disease severity and patient survival [4]. Importantly, high expression of these miRNAs was detectable before GvHD was diagnosed clinically [4,44]. However, our data did not show a positive correlation of miR-93* with GvHD status but instead we found that miR-93-5p, which is another strand of miR-93, was negatively correlated with GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that expression of miR-93*/ miR-93-3p together with miR-423, miR-199a-3p and miR-377 in the plasma was able to predict the probability of aGvHD occurrence and was furthermore positively associated with disease severity and patient survival [4]. Importantly, high expression of these miRNAs was detectable before GvHD was diagnosed clinically [4,44]. However, our data did not show a positive correlation of miR-93* with GvHD status but instead we found that miR-93-5p, which is another strand of miR-93, was negatively correlated with GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis and treatment of graft-versus-host disease (GVHD), the application of EVs has made more advancement. The EVs isolated from patient serum contains three miRNAs (miR-423, miR-199, miR-93), which may be related to the incidence and severity of GVHD [68]; and the expression of CD146, CD31, and CD140-α on EVs surface, is also closely related to the onset of the disease [69]. Traditional MSCs therapy after replacement with EVs for GVHD also showed ideal results, suggesting that MSCs-derived EVs are potential for cell-free therapy for GVHD [58,70].…”
Section: Evs As Therapymentioning
confidence: 99%
“…In earlier miRBase releases, a '*' was used to indicate the miRNA was the minor product of the precursor maturation process and not functional. However, as product from both arms has been subsequently shown to be functional [7] this suffix is gradually being retired from miRBase, although its usage continues in the literature [21][22][23][24][25][26]. Additionally, the species code has been modified over time to reflect changes in the accepted species name; for example, the species code for Capitella teleta (NCBI-taxid: 283909) was updated from cap to cte in version 15 (to reflect the change from 'Capitella sp' to 'Capitella teleta' as the commonly accepted name).…”
Section: Mirna Annotation In Mirbasementioning
confidence: 99%